Pretransplant Locoregional Therapy for Hepatocellular Carcinoma: Evaluation of Explant Pathology and Overall Survival - Beal, Eliza W.; Dittmar, Kristin M.; Hanje, A. James; Michaels, Anthony J.; Conteh, Lanla; Davidson, Gail; Black, Sylvester M.; Bloomston, P. Mark; Dillhoff, Mary E.; Schmidt, Carl R. (Frontiers in Oncology, 2016)
BACKGROUND AND OBJECTIVES: Liver transplant is an important treatment option for patients with hepatocellular carcinoma (HCC) within Milan Criteria. We sought to determine the rate of complete tumor necrosis after bridging therapy. METHODS: The medical records of all 178 patients undergoing liver transplantation between 1/1/2008 and 7/31/2015 were reviewed. Response to therapy by imaging was based on mRECIST criteria (Lencioni & Llovet, 2010). RESULTS: Sixty-three (35%) patients had HCC. Forty-three (68%) were treated with at least one bridging therapy and 14 (22%) were diagnosed incidentally. Eighteen (42%) underwent TACE and 25 (58%) underwent ablation. Twenty (80%) patients who underwent ablation and 9 (60%) who underwent TACE had complete response based on imaging. Viable tumor was identified in explant pathology in 32 patients (74%). The presence or absence of viable tumor was not associated with overall survival. CONCLUSION: Rates of viable tumor based on pathologic analysis in the hepatic explant were high after bridging therapy, but not associated with worse outcome. We conclude that serial bridging to achieve complete pathologic tumor response is not needed prior to transplant for HCC and presence of complete response by imaging is adequate. Further studies are needed to determine if cancer cells that appear viable are alive.